Development and validation of software for simulation of product processing regimes at an electron accelerator - Nikiforov, V.I.; Pelichatyi, N.M.; Pomatsalyuk, R.I.; Rogov, Yu.V.; Shevchenko, V.A.; Tenishev, A.Eh.; Uvarov, V.L. (Вопросы атомной науки и техники, 2013)
On the basis of the PENELOPE-2008 transport code, the three fundamental SW complexes for the modelling of processes in objects of various geometry and materials exposed to the scanned electron beam have been developed. For testing, the electron range and stopping power as well as photon absorption coefficients for different materials in the particle energy range 1…30 MeV were calculated. The results obtained were compared with the reference data given in the ICRU Report 35. At the second stage of validation, the computation and measurement of the absorbed dose in the standard polystyrene calorimeter as well as the dose distribution in the rectangular phantom passing via the zone of exposure to the scanned electron beam were conducted. Application of the developed SW enables the analysis and optimization of the industrial irradiation regimes. На основі транспортного коду PENELOPE-2008 розроблено три базові комплекси програм для моделювання процесів дії скануючого пучка електронів на об'єкти різної геометрії і з різних матеріалів. Для тестування розроблених програм на їх основі були розраховані пробіг і питомі втрати енергії електронів, а також масовий коефіцієнт ослаблення фотонів у різних середовищах у діапазоні енергії частинок 1…30 МеВ. Проведено порівняння отриманих результатів з референтними даними, що містяться в доповіді 35 МКРО. На другому етапі валідації були виконані розрахунок і вимірювання поглинутої дози в стандартному калориметрі з полістиролу, а також її розподілів в прямокутному фантомі, переміщуваних через зону дії скануючим пучком електронів. Застосування розробленого ПО забезпечує можливість аналізу та оптимізації режимів промислової обробки продукції на прискорювачі електронів. На основе транспортного кода PENELOPE-2008 разработаны три базовых комплекса программ для моделирования процессов воздействия сканирующего пучка электронов на объекты различной геометрии и из разных материалов. Для тестирования разработанных программ на их основе были рассчитаны пробег и удельные потери энергии электронов, а также массовый коэффициент ослабления фотонов в различных средах в диапазоне энергии частиц 1…30 МэВ. Проведено сравнение полученных результатов с референтными данными, содержащимися в докладе 35 МКРЕ. На втором этапе валидации были проделаны расчет и измерение поглощенной дозы в стандартном полистирольном калориметре, а также ее распределений в прямоугольном фантоме, перемещаемых через зону воздействия сканируемым пучком электронов. Применение разработанного ПО обеспечивает возможность анализа и оптимизации режимов промышленной обработки продукции на ускорителе электронов.